2020
DOI: 10.1101/2020.05.27.119578
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Theory and Simulations of condensin mediated loop extrusion in DNA

Abstract: The condensation of several mega base pair human chromosomes in a small cell volume is a spectacular phenomenon in biology. This process, involving the formation of loops in chromosomes, is facilitated by ATP consuming motors (condensin and cohesin), that interact with chromatin segments thereby actively extruding loops. Motivated by real time videos of loop extrusion (LE), we created an analytically solvable model, which yields the LE velocity as a function of external load acting on condensin. The theory fit… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 62 publications
2
1
0
Order By: Relevance
“…Interestingly, real-time imaging using the EQ mutant, which blocks the ATP hydrolysis of SMC proteins, showed the O-to-B shape transition, suggesting that the B-shape is induced by ATP binding to the head domains. This result is also supported by the recent Cryo-EM studies of human cohesin and yeast cohesin complexes showing that the hinge domain is engaged with the heads and HAWK (Collier et al, 2020;Higashi et al, 2020;Takaki et al, 2021).…”
Section: Controversial Structural Studies Of Smc Proteinssupporting
confidence: 69%
See 1 more Smart Citation
“…Interestingly, real-time imaging using the EQ mutant, which blocks the ATP hydrolysis of SMC proteins, showed the O-to-B shape transition, suggesting that the B-shape is induced by ATP binding to the head domains. This result is also supported by the recent Cryo-EM studies of human cohesin and yeast cohesin complexes showing that the hinge domain is engaged with the heads and HAWK (Collier et al, 2020;Higashi et al, 2020;Takaki et al, 2021).…”
Section: Controversial Structural Studies Of Smc Proteinssupporting
confidence: 69%
“…Moreover, recent in vivo studies of cohesin support that the hinge can be in close proximity with the head domain. Furthermore, the force-dependent step sizes observed by magnetic tweezers fits a simulation based on the scrunching model (Ryu et al, 2020b;Takaki et al, 2021). A recent study suggested a Brownian ratchet model in which the conformational changes between the O-and B-shapes are induced by thermal fluctuations due to the flexible SMC arms (Hwang and Karplus, 2019).…”
Section: Controversial Mechanisms For Dna Loop Extru-sionsupporting
confidence: 56%
“…Recent single-molecule experiments revealed that the budding yeast condensin is a molecular motor [6] that extrudes a DNA loop [7,8]. However, the detailed molecular mechanism of DNA-loop extrusion by condensin and other members of the SMC protein family remains unclear [8][9][10] and has been an ambitious target of computational modeling studies [11][12][13].…”
Section: Introductionmentioning
confidence: 99%